A Rare Case of Digital Ischemia and Gangrene in ANCA-Associated Vasculitis with Review of the Literature - Richard A. Lau; Ramandeep Bains; Duminda Suraweera; Jane Ma; Emil R. Heinze; Andrew L. Wong; Philip J. Clements (Case Reports in Rheumatology)
This paper describes one patient with Antineutrophil Cytoplasmic Antibody- (ANCA-) associated vasculitis who initially presented with multiple ischemic fingers and toes. On further evaluation, the patient was also found to have pulmonary-renal involvement and episcleritis. The diagnosis was supported with a positive cANCA (anti-proteinase 3) and a bronchoscopy consistent with diffuse alveolar hemorrhage. Although the patient refused a tissue biopsy, clinical presentation including nasal ulceration, sinus congestion, and epistaxis and anti-proteinase 3 antibody were more consistent with Granulomatosis with Polyangiitis (GPA) rather than Microscopic Polyangiitis (MPA) or Eosinophilic Granulomatosis with Polyangiitis (EGPA) based on the recently presented ACR/EULAR Provisional 2017 Classification Criteria for GPA (Luqmani et al., 2016). The patient responded well to therapy including high dose steroids and cyclophosphamide, with improvement of all organs involved and had no further digital ischemia or gangrene on follow-up. We include a review of the English literature summarizing presentation, management, and outcome of 16 similar cases.